1986
DOI: 10.1901/jeab.1986.45-237
|View full text |Cite
|
Sign up to set email alerts
|

Rule‐governed Behavior and Sensitivity to Changing Consequences of Responding

Abstract: Humans were presented with a task that required moving a light through a matrix. Button presses could produce light movements according to a multiple fixed-ratio 18/differential-reinforcement-oflow-rate 6-s schedule, with components alternating every 2 min. Moving the light through the maze earned points worth chances on money prizes. In Experiment 1 four conditions were assessed through between-subject comparisons: minimal instructions, instructions to press rapidly, instructions to press slowly, and instruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
239
4
68

Year Published

1987
1987
2015
2015

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 344 publications
(331 citation statements)
references
References 27 publications
(53 reference statements)
20
239
4
68
Order By: Relevance
“…Diversos estudos têm indicado que (a) a insensibilidade comportamental tende a ocorrer naquelas situações em que o responder continua produzindo conseqüências reforçadoras após a mudança, e (b) quanto maior a freqüência de reforços disponíveis na nova contingência, mais acentuada a persistência do responder (Buskist, Bennett, & Miller, 1981;Catania, Matthews, & Shimoff, 1982;Galizio, 1979;Hayes, Brownstein, Zettle, Rosenfarb, & Korn, 1986;Kaufman, Baron, & Kopp, 1966;Newman, Buffington & Hemmes, 1995). Resultados semelhantes foram observados no presente estudo: (a) os padrões de escolha apresentados por ambos os participantes continuaram gerando pontos após a reversão, o que contribuiu para a persistência do responder, e (b) a insensibilidade foi menos acentuada quando resultava em perdas dos reforços programados (Participantes 1).…”
Section: Discussionunclassified
“…Diversos estudos têm indicado que (a) a insensibilidade comportamental tende a ocorrer naquelas situações em que o responder continua produzindo conseqüências reforçadoras após a mudança, e (b) quanto maior a freqüência de reforços disponíveis na nova contingência, mais acentuada a persistência do responder (Buskist, Bennett, & Miller, 1981;Catania, Matthews, & Shimoff, 1982;Galizio, 1979;Hayes, Brownstein, Zettle, Rosenfarb, & Korn, 1986;Kaufman, Baron, & Kopp, 1966;Newman, Buffington & Hemmes, 1995). Resultados semelhantes foram observados no presente estudo: (a) os padrões de escolha apresentados por ambos os participantes continuaram gerando pontos após a reversão, o que contribuiu para a persistência do responder, e (b) a insensibilidade foi menos acentuada quando resultava em perdas dos reforços programados (Participantes 1).…”
Section: Discussionunclassified
“…Um problema, no entanto, que ainda não está claro nessa área de pesquisa, é a variabilidade nos resultados (relativos ao seguimento e ao não-seguimento de regras), frequentemente encontrada, dentro de uma mesma condição experimental, em alguns dos estudos (por exemplo, Albuquerque et al, 2003;Hayes, Brownstein, Zettle, Rosenfarb, & Korn, 1986;LeFrancois, Chase, & Joyce, 1988;Newman, Buffi ngton, & Hemmes, 1995;Oliveira & Albuquerque, 2007;Paracampo & Albuquerque, 2004;Shimoff, Catania, & Matthews, 1981).…”
unclassified
“…Changes to schedule-typical responding which subjects show upon the withdrawal of instructions suggest that following such rules may be interpreted as an instance of pliance (Hayes et al, 1986). Similarly, Hayes et al have suggested that differential effects of shaped versus experimenter-instructed rules (Catania et al, 1982) (Matthews et al, 1985) suggests that shaped guesses which specify particular ways of responding (e.g., "press fast") are more likely to exert such control than those merely tacting the relevant contingencies (e.g., "the button works after a random number of presses").…”
Section: Classesmentioning
confidence: 99%